The use of video job-aids to improve the quality of seasonal malaria chemoprevention delivery. - Susana Scott; Bienvenu Salim Camara; Michael Hill; Eugène Kaman Lama; Lansana Barry; Aurore Ogouyemi-Hounto; William Houndjo; Gauthier Tougri; Nombre Yacouba; Dorothy Achu; Marcellin Ateba; Mahamat Saleh Issakha Diar; et al. (PLOS Digital Health, 2022)
Mobile phones are increasingly used in community health programmes, but the use of video job-aids that can be displayed on smart phones has not been widely exploited. We investigated the use of video job-aids to support the delivery of seasonal malaria chemoprevention (SMC) in countries in West and Central Africa. The study was prompted by the need for training tools that could be used in a socially distanced manner during the COVID-19 pandemic. Animated videos were developed in English, French, Portuguese, Fula and Hausa, illustrating key steps for administering SMC safely, including wearing masks, washing hands, and social distancing. Through a consultative process with the national malaria programmes of countries using SMC, successive versions of the script and videos were reviewed to ensure accurate and relevant content. Online workshops were held with programme managers to plan how to use the videos in SMC staff training and supervision, and the use of the videos was evaluated in Guinea through focus groups and in-depth interviews with drug distributors and other staff involved in SMC delivery and through direct observations of SMC administration. Programme managers found the videos useful as they reinforce messages, can be viewed at any time and repeatedly, and when used during training sessions, provide a focus of discussion and support for trainers and help retain messages. Managers requested that local specificities of SMC delivery in their setting be included in tailored versions of the video for their country, and videos were required to be narrated in a variety of local languages. In Guinea, SMC drug distributors found the video covered the all the essential steps and found the video easy to understand. However, not all key messages were followed as some of the safety measures, social distancing and wearing masks, were perceived by some as creating mistrust amongst communities. Video job-aids can potentially provide an efficient means of reaching large numbers of drug distributors with guidance for safe and effective distribution of SMC. Not all distributors use android phones, but SMC programmes are increasingly providing drug distributors with android devices to track delivery, and personal ownership of smartphones in sub-Saharan Africa is growing. The use of video job-aids for community health workers to improve the quality delivery of SMC, or of other primary health care interventions, should be more widely evaluated.